A retrospective study of drug utilization and hospital readmissions among Medicare patients with hepatic encephalopathy. Issue 16 (April 2020) - Vadhariya, Aisha; Chen, Hua; Serna, Omar; Zamil, Hani; Abughosh, Susan M.
Abstract : Abstract: Hepatic encephalopathy (HE) is a complication occurring in patients with cirrhosis and is associated with neuropsychiatric and motor abnormalities. Symptomatic HE episodes almost always require hospitalization and the frequent recurrence of episodes is associated with poor prognosis and increased medical costs. The utilization of existing therapies for management of HE and adherence to them has yet to be evaluated using real-world claims data. The aim of this study was to evaluate HE drug regimens and adherence and their association with hospital readmissions in Medicare Advantage plan patients. This was a retrospective cohort study of patients discharged from a HE-related hospitalization or emergency room visit. Based on subsequent enrollment in the plan they were categorized into cohorts of 1 month, 3, and 6 months follow-up, and medication regimen was evaluated within the first month. The drugs evaluated included lactulose, rifaximin, and neomycin. Multivariable logistic regression was conducted to evaluate the association of drug regimen and medication adherence measured as proportion of days covered with HE readmissions. There were 347 patients hospitalized for HE with 184 patients having 30-day enrollment and either a drug refill or an outpatient visit in this duration. Medications were not refilled by 67 (36.4%) patients. Various drug regimens had different adherence with mean (standard deviation) proportion of days covered ranging from 0.56 (0.29) to 0.82 (0.16) at 3 months and 0.48 (0.3) to 0.77 (0.15) at 6 months. The results of logistic regression at 3 and 6 months did not show a significant association of medication use or medication adherence with hospital readmissions. Despite availability of therapy, medication utilization was alarmingly low after discharge of patients from HE-related hospitalization. Medication adherence was also low, which may affect the rate of recurrence and costs associated with readmissions. Efforts are needed in both care coordination of these patients to ensure they are prescribed appropriate medications and to enhance adherence to them.